Diastereospecific Bis‐alkoxycarbonylation of 1, 2‐Disubstituted Olefins Catalyzed by Aryl α‐Diimine Palladium(II) Catalysts. Issue 18 (20th April 2018) - Olivieri, Diego; Fini, Francesco; Mazzoni, Rita; Zacchini, Stefano; Della Ca', Nicola; Spadoni, Gilberto; Gabriele, Bartolo; Mancuso, Raffaella; Zanotti, Valerio; Carfagna, Carla
Abstract: Readily synthesized aryl α‐diimine derivatives have been used as efficient ligands for the palladium‐catalyzed oxidative bis‐alkoxycarbonylation reaction of 1, 2‐disubstituted olefins. The most active catalystA was formed in situ from bis‐(2, 6‐dimethylphenyl)‐2, 3‐dimethyl‐1, 4‐diazabutadiene and Pd(TFA)2 (TFA=trifluoroacetate). This catalytic system was able to selectively convert 1, 2‐disubstituted olefins into 2, 3‐disubstituted‐succinic diesters with total diastereospecificity, in good yields (up to 97%) with 2 mol% of catalyst loading, under mild reaction conditions (4 bar of CO at 20 °C in presence of p ‐ toluenesulfonic acid as additive and p ‐benzoquinone as oxidant). The optimized reaction conditions could be successfully applied to 1, 2‐disubstituted aromatic, aliphatic, cyclic olefins and to unsaturated fatty acid methyl esters, employing methanol or benzyl alcohol as nucleophiles. The use of the bulky, less reactive isopropyl alcohol has allowed to better understand the mechanisms involved in the catalytic process. The geometry of the carbonylated products can be explained as a consequence of a concerted syn addition of the Pd‐alkoxycarbonyl moiety to the olefin C=C bond. CatalystA was isolated, characterized and analyzed by single crystal X‐ray diffraction analysis. Abstract :